2021
DOI: 10.3390/ijms221810001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Axenfeld–Rieger Syndrome from Zebrafish foxc1 and pitx2 Mutants

Abstract: Axenfeld–Rieger syndrome (ARS) encompasses a group of developmental disorders that affect the anterior segment of the eye, as well as systemic developmental defects in some patients. Malformation of the ocular anterior segment often leads to secondary glaucoma, while some patients also present with cardiovascular malformations, craniofacial and dental abnormalities and additional periumbilical skin. Genes that encode two transcription factors, FOXC1 and PITX2, account for almost half of known cases, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…3,15,[24][25][26][27][28][29][30][31] Reports in the literature have suggested that FOXC1 mutations are more likely to cause isolated ocular findings such that craniofacial and dental anomalies are rare. 3,32 This is in contrast to PITX2 mutations, which in addition to anterior segment dysgenesis have been reported to be commonly associated with craniofacial abnormalities. 3,[32][33][34] Further, a more recent study showed that FOXC1 mutations had more corneal involvement and higher incidence of glaucoma in contrast to PITX2 mutations which showed more iris abnormalities.…”
Section: Ars Genetics and Pathogenesismentioning
confidence: 93%
“…3,15,[24][25][26][27][28][29][30][31] Reports in the literature have suggested that FOXC1 mutations are more likely to cause isolated ocular findings such that craniofacial and dental anomalies are rare. 3,32 This is in contrast to PITX2 mutations, which in addition to anterior segment dysgenesis have been reported to be commonly associated with craniofacial abnormalities. 3,[32][33][34] Further, a more recent study showed that FOXC1 mutations had more corneal involvement and higher incidence of glaucoma in contrast to PITX2 mutations which showed more iris abnormalities.…”
Section: Ars Genetics and Pathogenesismentioning
confidence: 93%
“…The most striking feature of Axenfeld–Rieger Syndrome (ARS) is developmental abnormalities in the anterior segment of the eye, leading to an increased risk of early-onset glaucoma. With loss-of-function techniques in zebrafish (CRISPR and morpholino), several zebrafish models have been reported to recapitulate the phenotypes of patients with ARS attributable to the foxc1 gene mutations (reviewed by [ 39 ]. Morales-Cámara et al (2021) [ 63 ] studied the involvement of guanylate cyclase activator 1C ( guca1c ) in the pathophysiology of primary congenital glaucoma through the generation of a guca1c knocked out zebrafish, which presented cell apoptosis and gliosis, with the Müller cells intensifying the expression of glial fibrillary acidic protein.…”
Section: Zebrafish As a Model For Ocular Pathologiesmentioning
confidence: 99%
“…Current data report an incidence of Xenfeld-Rieger syndrome in the population of 1: 200,000 while there is no definitive data on a gender and racial prevalence [9,10]. The mutation in genes of two transcription factors, FOXC1, FOXC2, FKHL7, PANCR and PITX2 [11][12][13][14], represent almost half of the known cases while the genetic defect is not known in 60%.…”
Section: Introductionmentioning
confidence: 99%